History and Story in the American Political Thriller Film: Hollywood in the Labyrinth - Castrillo Maortua, Pablo (Lexington Books, 2023)
In this book, Pablo Castrillo Maortua analyzes the emergence of the political thriller in Hollywood at a time of angst and turmoil in the United States. The Cold War, the nuclear age, domestic and international scandals, and an increasingly deceitful political culture catalyzed a filmmaking current that would gradually develop its own narrative form and aesthetics into a new genre. Castrillo Maortua explores the dramatic identity and design of the American political thriller, tracking the close correlation between the evolution of the genre and the history of the United States from the Cuban Missile Crisis to the 9/11 terrorist attacks and the ensuing War on Terror. Ultimately, the author demonstrates how the American political thriller defies Hollywood conventions and cultural presuppositions with an entertaining yet critical view of the state of politics. Scholars of film studies, screenwriting, and genre theory will find this book of particular interest.